KEADILAN RESTORATIF BAGI MASYARAKAT MISKIN - Sholahudin (Al'Adalah, 2015)
Injustice law phenomena this keep happening in the practice of law in this country. The emergence of all the action of protest against law enforcement officials in all areas, shows that the system and practices our laws are troubled. Our law enforcement, including on the poor community is very legalistic-positivistik only based on the rule of law formal written .The act of alternative criminal claim attempts should also be made by the state in the process of injustice law practices phenomena that befell the poor. The Country through law enforcement officials need to driven to promote and apply an criminal alternative claim to poor people, which is through approach “restorative justice”. Restorative justice will be institution that can be a equity justice, especially for the victims and the vulnerable sides in social-politics and weak economically, like the children, elderly, and the poor. Therefore, positive law of the state must to adopt elements of the existence of this “restorative justice”. Approach of this restorative justice is more humanistic and can give substantive justice to the poor people who comes to the law, than through the formal approach; legalistic-positivistic approach only express formal justice.